ANALISIS KREATIVITAS GURU DALAM PENGEMBANGAN MEDIA PEMBELAJARAN IPS DI MI MUNAWARIYAH PALEMBANG - Wulandari, Bintang; Maryani , Siti; Duesta Defini , Aldhea; Liza Apriel, Neshia; Dela, Dela (JIMR : Journal Of International Multidisciplinary Research, 2024)
The purpose of this study was to determine the Creativity of Teachers in the Development of Social Studies Learning Media at Mi Munawariyah Palembang.  One of the factors that greatly influences the success of the teaching and learning process in the classroom is having creative and professional teachers so that they can achieve optimal learning outcomes. This research uses a type of qualitative research method with a descriptive analysis approach. The study population consisted of principals, teachers, and students of class 5C MI Munawariyah. As for the sample in this study, we conducted research in class 5C with 21 students. The data analysis technique uses interactive analysis, namely data reduction, data presentation, and conclusion drawing. The results showed that teaching and learning teacher creativity is very influential on the learning process of students because it creates an effective and conducive learning environment. Innovative learning models can help teachers in applying the model to Mi social studies subjects. So that students develop creative thinking, responsibility and cooperation in solving learning problems, and when you write teaching materials, you can know that teachers are creative.